ANALISIS TINGKAT KREATIVITAS SISWA KELAS IV DALAM PEMBELAJARAN PRAKARYA MENGGUNAKAN METODE SURVEI - Farida, Alma; Sukma Nugraha, Widdy; Hidayati, Silmi; Aulia Zahra, Shindy; Nabella, Indirawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to analyze the level of creativity of fourth-grade students in craft learning using a survey method. The research employed a quantitative approach with a descriptive design. The population as well as the sample consisted of all fourth-grade students of SD Negeri 4 Mekarluyu, totaling 20 students, selected using a saturated sampling technique. The research instrument was a closed-ended questionnaire based on a Likert scale, which had been tested for validity and reliability. The reliability test showed a Cronbach’s Alpha value of 0.890, indicating a very high level of reliability. The data were analyzed using descriptive quantitative techniques by classifying the scores into three categories: high, medium, and low. The results revealed that 100% of the students were categorized in the medium level of creativity, with score ranges between 40–62. These findings indicate that students demonstrate basic creative abilities such as curiosity, flexibility, optimism, problem-solving skills, and imagination; however, they have not yet reached a high level of creativity. Therefore, more innovative and contextual teaching strategies are needed to enhance students’ creativity in craft learning.